Transient Spectroscopy of Dipyridophenazine Metal Complexes which undergo electron transfer with DNA - KELLY, JOHN (My University, 2011)
This review considers transient spectroscopic studies of electron transfer reactions between nucleic acids and the excited states of transition metal complexes containing dipyridophenazine or related ligands and focuses mainly on complexes of ruthenium, chromium and rhenium. Particular emphasis is placed on systems where transient UV/visible and/or infrared absorption spectroscopy have been employed.
PUBLISHED
Keywords: Biochemistry; ligands; Genes & Society